2020
DOI: 10.1364/optica.382989
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous III-V on silicon nitride amplifiers and lasers via microtransfer printing

Abstract: The development of ultralow-loss silicon-nitride-based waveguide platforms has enabled the realization of integrated optical filters with unprecedented performance. Such passive circuits, when combined with phase modulators and low-noise lasers, have the potential to improve the current state of the art of the most critical components in coherent communications, beam steering, and microwave photonics applications. However, the large refractive index difference between silicon nitride and common III-V gain mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…In terms of signal coherence, recent studies have shown that the phase noise of the soliton repetition frequency at 10's of GHz can be orders of magnitude smaller than that of its pump laser 5,[19][20][21] . When microresonator solitons are married with integrated lasers 22,23 , amplifiers 24 , and high-speed photodiodes 25 through heterogeneous or hybrid integration, a fully integrated mmWave platform can be created with high-power, high-coherence performance, and the potential for large-scale deployment through mass production ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of signal coherence, recent studies have shown that the phase noise of the soliton repetition frequency at 10's of GHz can be orders of magnitude smaller than that of its pump laser 5,[19][20][21] . When microresonator solitons are married with integrated lasers 22,23 , amplifiers 24 , and high-speed photodiodes 25 through heterogeneous or hybrid integration, a fully integrated mmWave platform can be created with high-power, high-coherence performance, and the potential for large-scale deployment through mass production ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, sophisticated assembly and packaging steps with high-precision alignment of the facets of the waveguides are required to achieve the high performance of such hybrid lasers [16], precluding costeffective scaling of manufacturing, especially in the case of devices with complex optical functionalities and high integration density, where many transitions between the active and passive sections are required. Heterogeneous integration of III-V semiconductor optical amplifiers onto Si 3 N 4 by micro-contact printing [17] has been proposed toward a more scalable solution.…”
Section: Introductionmentioning
confidence: 99%
“…As for the example considered here the effective mode area is relatively large and the pulse energies are low (< 2.2 pJ), it is presumed that nonlinear losses play a salient role in chip-scale mode-locked lasers with a silicon waveguide cavity. Switching to a silicon-nitride platform could hence be a valuable alternative to eliminate the detrimental effects of two-photon- and free-carrier absorption altogether 60 . In case (3), the pulse width and peak power respectively decrease and increase with injection current.…”
Section: Resultsmentioning
confidence: 99%